NGGUSU WARU–BASED SCHOOL LEADERSHIP AND LEARNING QUALITY IN INDONESIAN ELEMENTARY SCHOOLS - Ikhsan Maulana; Nur Indah Istiqomah; Anam Sutopo; Sabar Narimo (El Midad, 2026)
This study examines the essence of the life experiences of school principals in implementing the local wisdom values of Nggusu Waru to strengthen the quality of learning in elementary schools in Bima Regency. This study uses a qualitative approach with a phenomenological design, following the Miles and Huberman interactive model. Data collection was carried out through triangulation of methods and sources, including semi-structured in-depth interviews with five principals, participatory observation, and documentation studies. Participants were selected through purposive techniques and snowball sampling. Data analysis uses a combination of thematic analysis and phenomenological processes, as well as the preparation of textual and structural descriptions. The findings reveal five main themes: (1) spirituality (nggolo) as an ethical foundation; (2) multidimensional intelligence (smart) in contextual decision-making; (3) courage and patience (courage) as the motor of gradual transformation; (4) consistency and social relationships (nggahi-groba-groba-raba) in building collaboration; and (5) adequacy (capability) in the management of creative resources. The five themes form a holistic and contextual Nggusu Waru-based leadership model. The theoretical implications enrich the educational leadership literature with an indigenous perspective, while the practical implications become a reference for leadership development programs and the implementation of the Independent Curriculum. Longitudinal and comparative research between regions is recommended to strengthen the model's empirical base